Dexmedetomidine Attenuates Spinal Cord Ischemia-reperfusion Injury in Rabbits by Decreasing Oxidation and Apoptosis - Liu, Bingbing; Liang, Yatong; Huang, Weihua; Zhang, Hui; Zhou, Daiwei; Xiao, Xiaoshan (Current Molecular Medicine, 2023)
Background: In brain ischemia, dexmedetomidine (DEX) prevents glutamate and norepinephrine changes, increases nerve conduction, and prevents apoptosis, but the mechanisms are poorly understood. Objective: This study aimed at examining the protective effect and function of DEX on spinal cord ischemia-reperfusion injury (SCIRI) and whether the effect is mediated by oxidative stress and apoptosis (with the involvement of Bcl-2, Bax, mitochondria, and Caspase-3). Methods: Rabbits were randomly divided into the sham group, infusion/reperfusion (I/R) group, and DEX+I/R group. SCIRI was induced by occluding the aorta just caudal to the left renal artery for 40 min, followed by reperfusion. DEX was continuously administered for 60 min before clamping. The animals were evaluated for neuronal functions. Spinal cord tissues were examined for SOD activity and MDA content. Bcl-2, Bax, and Caspase-3 expressions were detected by western blotting. TUNEL staining was used for apoptosis. Results: With the extension of reperfusion time, the hind limbs’ neurological function in the DEX+I/R group gradually improved, but it became worse in the I/R group (all P<0.05 vs. the other time points within the same groups). Compared with I/R, DEX decreased MDA and increased SOD (P<0.01), upregulated Bcl-2 protein expression (P<0.05), downregulated Bax expression (P<0.05), decreased caspase-3 expression (P<0.05), prevented histological changes in neurons, and decreased the apoptotic index of the TUNEL labeling (P<0.05). Conclusion: DEX could attenuate SCIRI in rabbits by improving the oxidative stress status, regulating the expression of apoptosis-related proteins, and decreasing neuronal apoptosis.
Keywords: dexmedetomidine